Incursões no vivido por alunos-professores em cursos de pós-graduação lato sensu: em foco, a dimensão afetiva - Teles, Alda Maria Bispo dos Santos (2010)
The objective of this analysis is the affective dimension in the context of the experience of student-professors in lato sensu post-graduate courses. The theoretical reference upon which this study is based with respect to affectivity was Henri Wallon's Development Theory, and for the questions related to the postgraduate course, authors were selected who deal with this theme. Answers to the following guiding questions were sought out in order to attain these objectives: What are the reasons for professors to seek out lato sensu post-graduate courses? What does the experience of the course selected mean to these student-professors? What are the feelings and emotions experienced by them in the course and their instigating situations? Two higher education institutions that offer in-class courses and two hundred and one practicing student-professors who were regularly enrolled and attending lato sensu courses in the area of education during the period of 2007 to 2009 in these institutions participated in this research. Two different courses and fifteen class groups were researched. The research methods used were: impressionistic observation, a questionnaire and discussion groups. The application of these methods took place on the campuses of the participating institutions. The questionnaire responses were consolidated into charts which served as stimulating elements for group discussion. The research results showed that: a high proportion of the professors looked for lato sensu post-graduate courses as a means of continuing education; the lato sensu course provides a space for student-professors to find favorable conditions for interaction with professors and student-professors from other backgrounds, providing a rich learning experience that reflects in their teaching practice; continuing in academic life as a lato sensu student enables new views of the teaching profession and this causes feelings of happiness, satisfaction and enthusiasm, among others; the lato sensu post-graduate courses they take complement graduate studies; there are problems of a personal and professional nature that negatively affect better utilization of the course which causes, mainly, a feeling of sadness